A Key Issue in Bharati Mukherjee’s Novels: Case study of Cultural Shock - Dhawan, Amit; Kumar Sharma, Dinesh (International Journal of Psychosocial Rehabilitation, 2024)
Bharati Mukherjee is a Third World Feminist essayist whose main focus is onissues and concerns concerning South Asian women, particularly in India; yet, she claims thather views are more comparable to those of North American women. She differs from otherauthors in the way she handles her champions (Indian ladies outsiders), most notably with theirsocial stun, which evicts them from life, either directly or indirectly. Tara Banerjee in 'TheTiger's Daughter,' Dimple in 'Spouse,' Jyoti in 'Jasmine,' Devi in 'Abandon it to me,' three sisters- Padma, Parvathi, and Tara in 'Alluring Daughters,' and Tara in 'The Tree Bride,' alldemonstrate this. Despite the fact that the courageous women are portrayed as strong andassertive, they are nonetheless subjected to the 'culture stun' behaviour. They have a strongpotential for adaptability; they are well-positioned to modify their lives for the better, ifnecessary, as well as to acknowledge the painful truths of their life in any event. This study aimsto capture the core cause, the central notion that underpins the dilemma that so many fans of herworks are experiencing.